2014
DOI: 10.1245/s10434-014-3982-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival Paradox Between Stage IIB/C (T4N0) and Stage IIIA (T1-2N1) Colon Cancer

Abstract: T4N0 colon cancer had significantly worse oncologic outcomes than T1-2N1 cancer regardless of adjuvant chemotherapy. The survival paradox may result from the biologic aggressiveness of T4N0 colon carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 20 publications
2
72
1
Order By: Relevance
“…Cox proportional hazards models adjusted for stage (IIB/IIC [reference], IIIA), age ( ≤ 65 [reference], > 65), BMI ( < 25 [reference], ≥ 25), ASA (1,2 [reference], ), preoperative CEA ( ≤ 5 [reference], > ), Tumor location (right [reference], left), obstruction or perforation (no [reference], yes), Adjuvant Chemotherapy (no [reference], yes), examined lymph node ( < 12 [reference], ≥ ), tumor size ( < 5 [reference], ≥ ), histology (well, moderate [reference], poor, mucinous), LVI or PNI (no [reference], yes), radial margin status (negative [reference], positive).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cox proportional hazards models adjusted for stage (IIB/IIC [reference], IIIA), age ( ≤ 65 [reference], > 65), BMI ( < 25 [reference], ≥ 25), ASA (1,2 [reference], ), preoperative CEA ( ≤ 5 [reference], > ), Tumor location (right [reference], left), obstruction or perforation (no [reference], yes), Adjuvant Chemotherapy (no [reference], yes), examined lymph node ( < 12 [reference], ≥ ), tumor size ( < 5 [reference], ≥ ), histology (well, moderate [reference], poor, mucinous), LVI or PNI (no [reference], yes), radial margin status (negative [reference], positive).…”
Section: Resultsmentioning
confidence: 99%
“…Several explanations have been proposed for the inferior survival in stage IIB/IIC compared with that in stage IIIA, including improper en‐bloc resection, especially in cases of stage IIC; lower use of systemic chemotherapy in patients at stage IIB/IIC; stage migration due to inadequate node dissection; and aggressive biological characteristics . However, only a few studies have directly compared the survival rates of the two groups after adjusting for these proposed confounding factors . Moreover, these previous studies may be limited by long study periods of more than 10 years, which may not reflect the effects of modern treatment modalities in terms of surgical techniques and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing numbers of studies have reported that up to 20% of patients with stage II CRC will undergo tumor recurrence following resection [17,18]. There is a subgroup of patients with stage II CRC who have a worse clinical outcome than patients with stage III CRC presenting with up to two positive lymph nodes (stage IIIA) [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing numbers of studies have reported that up to 20% of patients with stage II CRC will undergo tumor recurrence following resection [17,18]. There is a subgroup of patients with stage II CRC who have a worse clinical outcome than patients with stage III CRC presenting with up to two positive lymph nodes (stage IIIA) [17,18]. Also, there is still controversy regarding the role of treatment with adjuvant chemotherapy (AC) for patients with stage II CRC who are at high risk of tumor recurrence [1921].…”
Section: Discussionmentioning
confidence: 99%
“…3 Similarly, Surveillance, Epidemiology, and End Results (SEER) studies highlighted that the survival rates of T1-2N1 patients were comparable to those in the T3N0 category, for both colon and rectal cancers. 4,5 Even though T4N0 and T1-2N1 cancers have been reported as small percentages of all colorectal neoplasms, 4,5 we would like to stress that a clear classification of risk groups could be crucial in identifying patients who could benefit (or conversely, not) of adjuvant treatments.…”
Section: Sub-staging Colorectal Cancers and Adjuvant Treatmentsmentioning
confidence: 99%